Novel coronavirus vaccine for promoting secretion of specific IgA antibody as well as construction method and application of novel coronavirus vaccine - WANG XINYUE; YANG HUI; SHAO DONGYAN; TIAN YIXIAO; HUANG QINGSHENG (2023)
The invention discloses a novel coronavirus vaccine for promoting secretion of a specific IgA antibody and a construction method and application thereof, belongs to the fields of immunology and genetic engineering, and aims to improve the IgA expression level of mucous membranes after vaccine immunization by using an immunogen (other structural proteins of novel coronavirus, such as N protein, E protein or M protein in the same way) researched and developed by using S protein as a vaccine. A set of novel coronavirus vaccine capable of remarkably promoting human B lymphocyte to secrete a specific anti-S protein IgA antibody and further enhancing mucous membrane protection and defense functions in the process that S protein stimulates immune response of a body is constructed, and a construction technology, a method and application of the novel coronavirus vaccine are provided. A novel vaccine of novel coronavirus modified by'adjuvant protein 'is formed by introducing a cluster of specific protein structural dom